Development of QR code-based learning card science and social studies to improve student outcomes - Putri Istianah; Galih Mahardika Christian Putra (Research and Development in Education (RaDEn), 2025)
Low student performance in local wisdom material, coupled with a lack of innovative learning media, has led to boredom and reduced enthusiasm during lessons. To address this issue, this study aimed to develop and evaluate a QR code-based learning card, known as PAS Cards (IPAS Learning Card, with IPAS referring to Ilmu Pengetahuan Alam dan Sosial or Science and Social Studies), to enhance learning outcomes for fourth-grade students at SDN Karanganyar 01. This research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The development process included expert validation, small- and large-group trials, and multiple data collection techniques such as observation, interviews, documentation, questionnaires, and tests. The media received high validation scores—96% from material experts and 97% from media experts—classifying it as “very feasible” for classroom use. Learning outcome data showed a significant improvement, with average scores increasing from 34 (pretest) to 87 (posttest). Furthermore, a 100% positive student response rate highlighted the media's effectiveness and appeal. These findings support using QR code-based learning cards as a practical and engaging tool to improve student achievement in science and social studies.